Gestational Age, Birth Weight, and Outcomes Six Years After the Norwood Procedure - Miller, Thomas A. (Pediatrics, 2019)
BACKGROUND: Preterm delivery and low birth weight (LBW) are generally associated with worse outcomes in hypoplastic left heart syndrome (HLHS), but an individual preterm or small neonate may do well. We sought to explore the interactions between gestational age, birth weight, and birth weight for gestational age with intermediate outcomes in HLHS. METHODS: We analyzed survival, growth, neurodevelopment, length of stay, and complications to age 6 years in subjects with HLHS from the Single Ventricle Reconstruction trial. Univariate and multivariable survival and regression analyses examined the effects and interactions of LBW (<2500 g), weight for gestational age, and gestational age category. RESULTS: Early-term delivery (n = 234) was more common than term (n = 219) delivery. Small for gestational age (SGA) was present in 41% of subjects, but only 14% had LBW. Preterm, compared with term, delivery was associated with an increased risk of death or transplant at age 6 years (all: hazard ratio = 2.58, confidence interval = 1.43–4.67; Norwood survivors: hazard ratio = 1.96, confidence interval = 1.10–3.49) independent of LBW and weight for gestational age. Preterm delivery, early-term delivery, LBW, and SGA were each associated with lower weight at 6 years. Neurodevelopmental outcomes were worst in the LBW cohort. CONCLUSIONS: Preterm delivery in HLHS was associated with worse survival, even beyond Norwood hospitalization. LBW, SGA, and early-term delivery were associated with worse growth but not survival. LBW was associated with worse neurodevelopment, despite similar length of stay and complications. These data suggest that preterm birth and LBW (although often concomitant) are not equivalent, impacting clinical outcomes through mechanisms independent of perioperative course complexity.